2014
DOI: 10.1111/1365-2745.12273
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation structure is as important as climate for explaining ecosystem function acrossPatagonian rangelands

Abstract: Summary1. Drylands cover about 41% of Earth's land surface, and 65% of their area supports domestic livestock that depends on the above-ground net primary productivity (ANPP) of natural vegetation. Thus, understanding how biotic and abiotic factors control ANPP and related ecosystem functions can largely help to create more sustainable land-use practices in rangelands, particularly in the context of ongoing global environmental change. 2. We used 311 sites across a broad natural gradient in Patagonian rangelan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 63 publications
6
56
1
6
Order By: Relevance
“…MAP contributed to the variation in shrub cover by 41.8% ( r = 0.647 ** ). This is consistent with previous studies which showed that precipitation was a major factor affecting shrub patch structures (Chen et al, ; Gaitán et al, ). Woody cover also significantly increased along increased rainfall gradients in Australian and South African savannah systems (Shackleton & Scholes, ; Williams, Duff, & Cook, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…MAP contributed to the variation in shrub cover by 41.8% ( r = 0.647 ** ). This is consistent with previous studies which showed that precipitation was a major factor affecting shrub patch structures (Chen et al, ; Gaitán et al, ). Woody cover also significantly increased along increased rainfall gradients in Australian and South African savannah systems (Shackleton & Scholes, ; Williams, Duff, & Cook, ).…”
Section: Discussionsupporting
confidence: 93%
“…Root competition for water in xeric regions might also affect patch size and spacing between them (King & Woodell, ). Positive relationship between species diversity of interspace grass (H′) and shrub cover ( r = 0.557 * ) was consistent with previous studies (Chen et al, ; Gaitán et al, ; Hao et al, ; Koyama, Sasaki, Jamsran, & Okuro, ; Ravolainen et al, ). In tundra, shrubs with highly broken forms are usually accompanied by low grass diversity and richness (Ravolainen et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…There is also increasing evidence that biotic attributes, such as cover and species richness (SR), also influence ecosystem functioning [8]. The diversity-ANPP relationship in response to drought has been assessed in experimental grasslands [9], but it is largely unknown how biotic attributes modulate this relationship at regional scales [10].…”
Section: Introductonmentioning
confidence: 99%
“…The average relative humidity for summer and winter are 25.5% and 65.6% respectively, while the evaporation reached 329.5 (mm) in summers and 53 (mm) in winters. The annual rainfall rate reaches about 656.05 mm, therate of annualtemperature19.6 c 0 , the annual rate of humidity45% and the amount rate of annual evaporation 162.7mm as in table (1).The nature of the alluvial soil and its fertility all these factors enhanced the growth and good distribution of the vegetative cover in this area .The botanical species as in table (2) refers to about 39 plant families, 85 genuses and 92 species. While the percentage of coverage was 95 % and plant density reached 395.48 plant/m 2 in the study region.…”
Section: Results and Discussion:-mentioning
confidence: 92%
“…Maintaining and enhancing vegetation cover and species richness, particularly in grassescould reduce the adverse effects of climate change on ecosystem functioning in these ecosystems [1].Ecological factors play a fundamental role in vegetation In particular; germination, growth and distribution. Flora is adapted to the ecological conditions everywhere, such as dry land plants, semi dry land plants or xerophytes and hydrophytes.…”
Section: Introduction:-mentioning
confidence: 99%